Carbon dioxide reduction through advanced conversion and utilization technologies - Zheng, Yun (Chemical engineer) (Boca Raton : Taylor & Francis, CRC Press, 2019)
Carbon Dioxide Reduction through Advanced Conversion and Utilization Technologies covers fundamentals, advanced conversion technologies, economic feasibility analysis, and future research directions in the field of CO2 conversion and utilization. This book emphasizes principles of various conversion technologies for CO2 reduction such as enzymatic conversion, mineralization, thermochemical, photochemical, and electrochemical processes. It addresses materials, components, assembly and manufacturing, degradation mechanisms, challenges, and development strategies. Applications of conversion technologies for CO2 reduction to produce useful fuels and chemicals in energy and industrial systems are discussed as solutions to reduce greenhouse effects and energy shortages. Particularly, the advanced materials and technology of high temperature co-electrolysis of H2O and CO2 to produce sustainable fuels using solid oxide cells (SOCs) are reviewed and the introduction, fundamentals, and some significant topics regarding this CO2 conversion process are discussed. This book provides a comprehensive and clear picture of advanced technologies in CO2 conversion and utilization. Written in a clear and detailed manner, it is suitable for students as well as industry professionals, researchers, and academics.
OCLC-licensed vendor bibliographic record.
Keywords: Carbon dioxide -- Separation; Electrolytic reduction; Carbon dioxide -- Recycling; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; SCIENCE / Energy; TECHNOLOGY / Engineering / Chemical & Biochemical